“Let me tell you what I think about online psychological help.” A thematic analysis of voluntary opinions collected at the onset of the COVID-19 pandemic - Wesołowski, Arkadiusz; Skawińska, Julianna; Soroko, Emilia (Frontiers in Psychology, 2023)
The COVID-19 pandemic shifted many aspects of life from face-to-face to an online form, including psychological help. Many people had to face the choice of adjourning contact with a psychologist or shifting it to the Internet. This study aimed to develop an understanding of attitudes and opinions toward relatively new phenomenon in Poland - online psychological help. Seventy two (N=72) statements about relationship between COVID-19 pandemic and online psychological help from (potential) patients were included in this research. The statements were collected from a community sample via open-ended question for volunteers added to an online survey conducted regarding an existing project. The statements were exclusively written responses to the following question: If you want to provide us with something about the relationships between the COVID-19 pandemic and online help/psychotherapy, please let us know below. By reason of exploratory character of our study and general phenomenological philosophical approach and constructionist approach, a thematic analysis method was used to analyze the data. The analysis led us to identify three general themes with sub-themes that refer to meaningful aspects of online psychological help: 1. Online psychological help situates in the shadow of face-to-face psychological help, 1.1. It frustrates users' needs, especially the need for psychological contact, 1.2. It contributes to negative emotions, 1.3. It is sometimes better than the face-to-face psychological help; 2. Online psychological help is a solution during the COVID-19 pandemic, 2.1. It provides a sense of continuity during lockdown, 2.2. It is a means to adapt to exceptional circumstances, 3. The concerns about the credibility and effectiveness of online psychological help. The results show (potential) patients’ attitudes (including emotions, thoughts, and concerns) toward online psychological help. The perspective presented here could be beneficial to professionals. A better understanding of client/patient attitudes will allow for more accurate customization of the online help and sensitize psychologists to the emotions that may occur about online psychological help. It could also be beneficial for patients to understand how other people would feel about online psychological help and develop ones’ own self-awareness of the attitudes toward online psychological help.